Pengaruh Budaya Religius Terhadap Kecerdasan Spiritual Peserta Didik Di SD Negeri 2 Cihaur - Hamidiana, Umiliah Maulida; Usamah, Asep (Jurnal Keislaman, 2024)
Culture is the result of human work, creativity and initiative that can be accepted by society, or a certain community, and carried out consciously without coercion in everyday life, and taught to the next generation simultaneously. Religious is a student's way of thinking and behaving based on religious values. Spiritual intelligence is intelligence that comes from within us and is associated with knowledge that exists outside our ego or conscious soul. Based on the problem formulation, the aim of this research is first, to find out whether there is an influence of religious culture on the spiritual intelligence of students at SD Negeri 2 Cihaur. second, to find out how religious culture influences the spiritual intelligence of students at SD Negeri 2 Cihaur. This type of research uses a quantitative approach with survey methods. The research results show that religious culture has a significant effect on students' spiritual intelligence. This is proven based on the results of analysis using tests in the form of questionnaires, calculations carried out using the Pearson product moment correlation test to determine the sig value. 0.008 < 0.05, then H0 is rejected and Ha is accepted, so the researcher concludes that there is an influence of religious culture on the spiritual intelligence of students at SD Negeri 2 Cihaur.